The International Conference on Information Network 2012 2012
DOI: 10.1109/icoin.2012.6164402
|View full text |Cite
|
Sign up to set email alerts
|

SISO polarized flat fading channel modeling for dual-polarized antenna systems

Abstract: The next-generation wireless systems are expected to support data rates of more than 100 Mbps in the outdoor environment. In order to support such large payloads, the polarized antenna can be employed as one of candidate technologies. Recently, the third generation partnership standards bodies (3GPP/3GPP2) have defined a cross-polarized channel model in SCM-E for MIMO systems, but this model is quite complex and too many parameters are included. The SCM-E channel model generates only single channel output for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As shown in Figure 1, the MS mobility is taken into consideration in regard to the polarized antenna channel model found in [11]. is the phase rotation of the received signal at the MS due to the scatterers, and is the updated phase rotation according to the MS movement, as described by where is the radius of the scatterers and Δ is the moving distance of the MS for a 1-packet duration (e.g., 5 us).…”
Section: The 2d Scatterer Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 1, the MS mobility is taken into consideration in regard to the polarized antenna channel model found in [11]. is the phase rotation of the received signal at the MS due to the scatterers, and is the updated phase rotation according to the MS movement, as described by where is the radius of the scatterers and Δ is the moving distance of the MS for a 1-packet duration (e.g., 5 us).…”
Section: The 2d Scatterer Modelmentioning
confidence: 99%
“…In addition, according to the scatterer environments, they are further classified into a 2D channel model and a 3D channel model. The PS multipolarized channel models are based on SCM-E channel model given by (11). It is a well-known 2D PMIMO channel model, which obtains only a single complex output resulting from the combination of all the polarized links.…”
Section: Proposed Practical and Simple Multipolarized Channel Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In related works, the authors in [7] provided a comparison of several multipolarized MIMO models and also presented some useful results in terms of channel capacity. In [8], the authors showed that the use of polarization diversity with a combining method enhances the capacity of wireless communication systems. Oestges et al in [1] studied the advantages of using DP antenna arrays in a multiple channel environment.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the multiple-inputmultiple-output (MIMO) systems, for saving the space, dual-polarized antennas are usually used to substitute two space-isolated singlepolarized antennas [6]. Such polarized MIMO antennas have been proved to show the advantages of increasing spectrum efficiency, mitigating polarization mismatch between the transmitter and the receiver, improving the channel capacity and diversity gain [7][8][9].…”
Section: Introductionmentioning
confidence: 99%